1999
DOI: 10.1016/s0022-5347(01)61930-x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function Following High Energy Microwave Thermotherapy: Results of a Randomized Controlled Study Comparing Transurethral Microwave Thermotherapy to Transurethral Prostatic Resection

Abstract: Although clinically less effective, high energy transurethral microwave thermotherapy is a better therapeutic option than surgery for patients who want to preserve sexual function. In particular ejaculation is often preserved after transurethral microwave thermotherapy while there is significant deterioration following transurethral prostatic resection. In general, older patients have greater sexual dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 27 publications
1
32
0
1
Order By: Relevance
“…Reoperation rates for TUMT were derived from two RCTs. 86,87 However, the AHCPR guideline is over 10 years old and its authors admit that very few studies reported symptom scores and that those that did used many different methods. 84 Although this limitation is allowed for to some extent in the wide confidence interval (CI) for this estimate (see Accounting for uncertainty in Chapter 10, p.112), the relationship between degree of symptom improvement and probability of retreatment is unclear.…”
Section: Effectivenessmentioning
confidence: 99%
“…Reoperation rates for TUMT were derived from two RCTs. 86,87 However, the AHCPR guideline is over 10 years old and its authors admit that very few studies reported symptom scores and that those that did used many different methods. 84 Although this limitation is allowed for to some extent in the wide confidence interval (CI) for this estimate (see Accounting for uncertainty in Chapter 10, p.112), the relationship between degree of symptom improvement and probability of retreatment is unclear.…”
Section: Effectivenessmentioning
confidence: 99%
“…First, as the symptoms become less bothersome, patients may feel less 'disabled' by their urinary symptoms and may thus be better able to enjoy other facets of life Sexual effects of medical therapy for benign prostatic hyperplasia DJ Carbone and S Hodges without feeling inhibited or limited. 55 Alternatively, inhibition of the a 1 -and a 1D -adrenoreceptor subtypes that predominate in cavernosal smooth muscle should facilitate erection. 56 The mechanism by which a-blockers affect the erectogenic response is via relaxation of the smooth muscle in the penile arteries or the corpora cavernosum, thus improving the inflow of blood.…”
Section: Medical Therapy For Bphmentioning
confidence: 99%
“…Although ejaculatory pain in the general male population is considered to be 1%, 1 it is presented a serious problem for 88-91% of men who experience it. 2,3 It can be caused by prostatectomy, 4,5 a history of prostatitis, 6 pelvic radiation, 7,8 lower urinary tract symptoms (LUTS) diagnosed with clinical benign prostatic hyperplasia (BPH), 9,10 chronic pelvic pain disorder, 11 and neuroleptics. [12][13][14][15][16][17][18] On the other hand, PE as a sole entity is rare, and its etiology often remains unknown.…”
Section: Introductionmentioning
confidence: 99%